Bacterial Isolates of Early Onset Neonatal Sepsis and Their Antibiotic Susceptibility Pattern - Mannan, Md Abdul; Iqbal, Shahed; Karim, SM Rezaul; Ahmed, Talim Uddin; Khan, Md Hakimul Haque; Ahmed, Ashraf Uddin; Dey, Subir; Yasmin, Sabina; Ferdous, Navila (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2018)
Background: Neonatal infections are the commonest cause of neonatal mortality along with perinatal asphyxia and consequence of Prematurity and Low Birth Weight (LBW) in Bangladesh. Early Onset Neonatal Sepsis (EONS) is neonatal sepsis occurring within the first 72 hours of birth and it is much more fulminant and has a higher mortality than Late Onset Sepsis (LOS). Sepsis in neonate remains a significant cause of mortality and morbidity in developing countries. Changing bacterial flora and emergence of resistant strains adds to the problem. Thus, neonatal sepsis requires accurate and timely clinical and laboratory diagnosis and proper management for better outcome. The organisms responsible for Early Onset Sepsis (EOS) are different than Late Onset Sepsis (LOS). In this study an attempt has been made to know the positivity rate of EOS and profile of bacteria responsible for EOS and determine the antimicrobial sensitivity pattern that were investigated for rule out sepsis. Methods: This was a prospective observation single centre study over a period of nine months (January to September, 2017) conducted on neonates born at Ad-din Medical College Hospital (AMCH), Dhaka and subsequently admitted in Neonatal Intensive Care Unit (NICU) within 72 hours of birth that were investigated for rule out sepsis. Dual blood sample for cultures from separate area along with essential investigations were sent by collecting samples under aseptic precautions. Empirical antimicrobial therapy was started according to antimicrobial guidelines in the NICU. The blood cultures test were carried out by BD BACTEC automated blood culture system and susceptibility testing was done for all blood culture isolates according to the criteria of the National Committee for Clinical Laboratory Standards by disk diffusion method. Results: A total of 700 neonates were investigated to rule out sepsis and 5.43% neonates were found with culture proven sepsis in the study. The gram positive bacteria accounted for 71% and gram negative 29% of the total isolates. Out of total 38 isolates, Coagulase-Negative Staphylococci (CONS) (68.4%) was the commonest followed by Acinetobacter (18.4%) and E. coli (7.9%) was common culture isolates. Among the gram positive, CONS (96.3%) was commonest isolate and in gram negative Acinetobacter (63.6%) was the most prevalent bacteria followed by E.coli (27.3%). Gram positive isolate, especially CONS (68.4%) was the major culprit for the early onset sepsis. Among the commonly used antibiotics, the susceptibilities were remarkably low to Amikacin (16%) in comparison to Ampicillin (42%) Cefotaxime (45%) and moderately high to Gentamicin (58%) for both gram positive & gram negative isolates. All (100%) gram positive isolates were resistant to Amikacin. Majority of the gram positive showed low susceptibilities to Meropenem (22%) Ciprofloxacin (41%) Ampicillin (48%) & Oxacillin (48%) in comparison to Cefotaxime (52%) Levofloxacin (55%) Gentamicin (70%), Linezolid (70%) and Vancomycin (74%). 50% of Coagulase Negative Staphylococcus (CONS) were resistant to Methicillin/Oxacillin. The sensitivity pattern of majority of gram negative isolates showed high level of resistance to Piperacillin+Tazobacterm (9%) and Ampicillin (27%) Gentamicin (27%) Cefotaxime (27%) less sensitive to Ciprofloxacin (45%); moderately high to Levofloxacin (54%) & Amikacin (54%) and highly sensitive to Imipenem/Meropenem (73%) & Colistin (91%). Gentamicin (58%) and Levofloxacin (55%) were showed marginal superiority compared to Ampicillin (42%) and Cefotaxime (45%) for effective coverage of both. Conclusion: Present study indicated that gram positive species especially CONS continue to be the predominant causative organism followed by Acinetobacter and E. coli in gram negative species. The antibiotic susceptibility profile suggested that for a given cohort empiric (initial) choice of Ampicillin and Gentamicin in EOS. Routine bacterial surveillance and their sensitivity patterns must be an essential component of neonatal care Chatt Maa Shi Hosp Med Coll J; Vol.17 (1); Jan 2018; Page 3-8